WOMEN’S SOCIAL NETWORKING AS A SOURCE OF THEIR SOCIAL EMPOWERMENT IN SLUM AREA OF MULTAN - Nazia Mushtaq; Amna Mushtaq; Mushtaq Naz (International Journal of Contemporary Issues in Social Sciences, 2024)
Social Networking is a source of social capital among women in which they are connecting themselves with social institutions and their structural settings. Through social ties, women explore new social and economic resources to empower themselves. They also have formal and informal opportunities to get social benefits from these resources. The current study is aimed to explore social factors associated with social networking and social empowerment of women in slum area of Multan District, South Punjab region of Pakistan. The study carried qualitative research approach in which 20 (women) respondents selected through purposive sampling. These twenty case studies of respondents selected who earned less than and equal to one dollar per day (Daily wage labor community). They interviewed by using interview guide as a research tool. Thematic Discourse analysis used to analyze impact of social factors on women’s social networking and their social empowerment. Social factors including education Attainment, social networking in labor class, interlink between upper and lower class, support of caste system, social support for physical disable people of community, role of socio-political networking on labor class, right of decision power in family, financial support from peer group, economic distribution for family development plan, formal and informal economic source of social networking play a important role impacting social status and living standard of women’s labor community of slum area. Formal and informal social measures should be taken to enhance their social and economic status for their better survival in a society.